Epidemiology, tumor characteristics and survival in patients with angiosarcoma in the United States: a population-based study of 4537 cases. (15th October 2019) - Zhang, Chao; Xu, Guijun; Liu, Zheng; Xu, Yao; Lin, Feng; Baklaushev, Vladimir P; Chekhonin, Vladimir P; Peltzer, Karl; Mao, Min; Wang, Xin; Wang, Guowen; Zhang, Chao
Abstract: Objective: Limited by sample size, angiosarcoma was rarely studied. We aimed to investigate the characteristics and prognosis of angiosarcoma in the National Cancer Institute's Surveillance, Epidemiology and End Results database. Methods: Patients who were diagnosed with primary angiosarcoma from 1973 to 2014 were extracted from the Surveillance, Epidemiology and End Results database. Kaplan–Meier analysis was used to estimate the overall survival, and the difference between groups was tested by the log-rank test. Multivariate Cox regression analyses were employed to identify prognostic factors for primary angiosarcoma. Results: A total of 4537 patients with angiosarcoma were included with the median age of 69 years. The median overall survival was 82.1 (95% confidence interval: 76.5–87.7) months. Overall 1-, 2- and 5-year survival rates were 55.2 ± 0.7, 41.0 ± 0.7 and 26.3 ± 0.7%, respectively. In the univariate analysis, age, gender, marital status, race, primary site, tumor grade, tumor size, Surveillance, Epidemiology and End Results historic stage and the surgery of primary site were significantly associated with overall survival. Multivariate Cox regression showed that factors including the patients older than 69 years, male, unmarried status, other primary sites, grades (III and IV), tumor size ≥ 5 cm, regional and distant stage and non-surgery were independently associated with poor survival. The results were consistent after excluding the patients in IV stages. Conclusions: This large population-based study comprehensively described the survival rate and prognostic factors for angiosarcoma in the United States. Age, gender, marital status, primary sites, tumor grade and size and historic stage were determinants of survival, and surgery can improve the prognosis of patients with angiosarcoma. Abstract : The median survival was 82.1 months and 5-year survival rate was 26.3% for patients with angiosarcoma in the United States. Age, gender, marriage, primary site, grade, size, historic stage and surgery were significant predictors.